1995
DOI: 10.1145/217839.217848
|View full text |Cite
|
Sign up to set email alerts
|

Profile-guided receiver class prediction

Abstract: The use of dynamically-dispatched procedure calls is a key mechanism for writing extensible and flexible code in object-oriented languages. Unfortunately, dynamic dispatching imposes a runtime performance penalty. Some recent implementations of pure object-oriented languages have utilized profile-guided receiver class prediction to reduce this performance penalty, and some researchers have argued for applying receiver class prediction in hybrid languages like C++. We performed a detailed examination of the dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Previous work on offline optimization of object-oriented languages demonstrated that using context-sensitive trace profiling can enable significant improvements in the effectiveness of profile directed inlining [13]. The goal of our work is to achieve these benefits online in a virtual machine.…”
Section: Context Sensitivity Overview and Motivationmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work on offline optimization of object-oriented languages demonstrated that using context-sensitive trace profiling can enable significant improvements in the effectiveness of profile directed inlining [13]. The goal of our work is to achieve these benefits online in a virtual machine.…”
Section: Context Sensitivity Overview and Motivationmentioning
confidence: 99%
“…Unlike Jikes RVM and the IBM DK, HotSpot only gathers call edge data during initial interpretation of a method and thus is vulnerable to mispredictions if the application's calling patterns are different during initialization and steady state execution. The Vortex optimizing compiler used offline contextsensitive profile data to guide its inlining decisions [13]. Vortex demonstrated that making inlining decisions using context-sensitive profile data can be quite valuable in optimizing object-oriented programs: context-sensitive profile data enabled speedups of up to 24% over context-insensitive profile data for large Cecil programs.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations